Possessions. Book two, The ghost table - Fawkes, Ray (Possessions, 2011)
Ms. Llewellyn-Vane is throwing a dinner party and all the specters are invited! The ghouls of the house for captured spirits and ghostly curiosities are playing host to Ms. Carter-Hawthorne's collection of rare apparitions and the Gurgazon is trying to be on its best behavior. But how long before the pit demon's true nature gets the better of it?